Allergic patients during the COVID‐19 pandemic—Clinical practical considerations: An European Academy of Allergy and Clinical Immunology survey. Issue 1 (17th January 2022) - Alvaro‐Lozano, Montserrat; Sandoval‐Ruballos, Mónica; Giovannini, Mattia; Jensen‐Jarolim, Erika; Sahiner, Umit; Tomic Spiric, Vesna; Quecchia, Cristina; Chaker, Adam; Heffler, Enrico; Klimek, Ludger; Brough, Helen; Sturm, Gunter; et al.
Abstract: Background: The COVID‐19 pandemic has affected health care systems unexpectedly. However, data focusing on practical considerations experienced by health care professionals (HCPs) providing care to allergic patients is scarce. Methods: Under the framework of the European Academy of Allergy and Clinical Immunology (EAACI), a panel of experts in the field of immunotherapy developed a 42‐question online survey, to evaluate real‐life consequences of the COVID‐19 pandemic in allergy practice. Results: The respondents in the survey were 618. About 80% of HCPs indicated being significantly affected in their allergy practice. A face‐to‐face visit reduction was reported by 93% of HCPs and about a quarter completely interrupted diagnostic challenges. Patients with severe uncontrolled asthma (59%) and anaphylaxis (47%) were prioritized for in‐person care. About 81% maintained an unaltered prescription of inhaled corticosteroids (ICS) in asthmatics. About 90% did not modify intranasal corticosteroids (INCS) in patients with allergic rhinitis. Nearly half of respondents kept biological prescriptions unmodified for asthma. About 50% of respondents kept their allergen immunotherapy (AIT) prescription patterns unchanged for respiratory allergies; 60% for insect venom allergies. Oral immunotherapy (OIT) for food allergies was initiated by 27%. About 20% kept carrying out up‐dosing without modifications and 14% changed to more prolonged intervals. Telemedicine practice was increased. Conclusions: HCPs providing care to allergic patients were affected during the pandemic in diagnostic, management, and therapeutic approaches, including AIT for respiratory, insect‐venom, and food allergies. Most HCPs maintained controller treatments for both asthma, and allergic rhinitis consistent with international recommendations, as well as biological agents in asthma. Remote tools are valuable in delivering allergy care.